Solve for u -1/3=-5/6+u

Math
-13=-56+u
Rewrite the equation as -56+u=-13.
-56+u=-13
Move all terms not containing u to the right side of the equation.
Tap for more steps…
Add 56 to both sides of the equation.
u=-13+56
To write -13 as a fraction with a common denominator, multiply by 22.
u=-13⋅22+56
Write each expression with a common denominator of 6, by multiplying each by an appropriate factor of 1.
Tap for more steps…
Multiply 13 and 22.
u=-23⋅2+56
Multiply 3 by 2.
u=-26+56
u=-26+56
Combine the numerators over the common denominator.
u=-2+56
Add -2 and 5.
u=36
Cancel the common factor of 3 and 6.
Tap for more steps…
Factor 3 out of 3.
u=3(1)6
Cancel the common factors.
Tap for more steps…
Factor 3 out of 6.
u=3⋅13⋅2
Cancel the common factor.
u=3⋅13⋅2
Rewrite the expression.
u=12
u=12
u=12
u=12
The result can be shown in multiple forms.
Exact Form:
u=12
Decimal Form:
u=0.5
Solve for u -1/3=-5/6+u

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top